(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يتناول البحث أثر نمط القيادة الديمقراطي في مقاومة التغيير لدى العاملين الإداريين في جامعة حلب من خلال دراسة العلاقة بين نمط القيادة الديمقراطي, وأبعاد مقاومة التغيير التنظيمية والموضوعية والاجتماعية والاقتصادية والثقافية. بالإضافة إلى دراسة الفروق بين العاملين في مقاومتهم للتغيير تبعاً لبعض المتغيرات الشخصية كالجنس والعمر والمؤهل العلمي والدخل الشهري والحالة الاجتماعية. استخدم الباحث المنهج الوصفي التحليلي, وتم توزيع استبانة على (308) عمال من العاملين الإداريين في جامعة حلب, وكان من أهم نتائج البحث: 1- يقاوم العاملون الإداريون في جامعة حلب التغيير لأسباب عديدة منها: عدم وجود اتصالات جديدة مع قادة التغيير, وعدم إدراكهم للأسباب الحقيقة للتغيير, وعدم مشاركتهم في عملية التغيير, وعدم واقعية التغيير من وجهة نظرهم, واعتقادهم بأن التغيير يؤدي إلى تغيير طبيعة العلاقات الاجتماعية القائمة بين العاملين, وخوفهم من فقدان بعض الامتيازات التي يتمتعون بها, واعتقادهم بأن السلوك الجديد المفترض يتعارض مع السلوك المعمول به حالياً في الجامعة. 2- هناك علاقة ارتباط عكسية بين استخدام المديرين لنمط القيادة الديمقراطي, وأبعاد مقاومة التغيير, أي كلما زاد استخدام المديرين لنمط القيادة الديمقراطي انخفضت مقاومتهم للتغيير بأبعادها المختلفة. 3- لا تختلف مقاومة العاملين الإداريين في جامعة حلب للتغيير باختلاف الخصائص الشخصية الآتية: الجنس, العمر, المؤهل العلمي, الدخل الشهري, الحالة الاجتماعية. This research deals with the impact of driving style democratic resistance to change at the administrative staff at the University of Aleppo through the study of the relationship between the Democratic leadership style, and the dimensions of the organizational resistance to change, objectivity, social, economic and cultural rights. In addition to the study of the differences between working in their resistance to change depending on certain variables, such as race, age, personal and academic qualification and monthly income and marital status. The researcher used the descriptive analytical method, were distributed a questionnaire to (308) factor of the administrative staff at the University of Aleppo, and it was the most important results: 1 - resists workers administrators at the University of Aleppo change for many reasons, including: the lack of new contacts with the leaders of the change, and lack of awareness of the causes of the truth for a change, and non-participation in the process of change, and the lack of real change from their perspective, and their belief that change leads to changing the nature of social relationships among workers, and fear of losing some privileges that they enjoy, and their belief that the new behavior is incompatible with the supposed behavior currently in place at the university. 2 - There is an inverse correlation between the use of managers to democratic leadership style, and the dimensions of resistance to change, that is, the greater the managers use a democratic style of leadership, the lower the resistance to change its various dimensions. 3- no different resistance administrative staff at the University of Aleppo to change depending on the personal characteristics of the following: gender, age, educational qualification, monthly income, marital status.